(untitled) - Badger, Ian (Thành phố Hồ Chí Minh, 2014)
Understand what they're saying - however they say it This completely innovative self-study book and audio CD set is the perfect way for busy executives to improve their English listening skills. It features real people talking about their work and their lives in a variety of native and non-native accents alongside exercises and learning material.
Keywords: English language,Tiếng Anh,Business communication,Giao tiếp kinh doanh,English language,Tiếng Anh; Business English,Tiếng Anh thương mại,Business English,Problems, exercises, etc.,Tiếng Anh thương mại,Câu hỏi, bài tập,vv